Loan shark: why/how youth chose loan sharking as an occupation? - Loi, Chai Ken; Rodriguez, Adriana Maria Ortega; Abdullah, Haslinda (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Generally speaking, Loan Shark refers to those individuals or organizations that lend money at excessively and often illegally high rates of interest; and tend to use violent and harsh methods to collect debts. In Malaysia, there are on-going cases of helpless borrowers been beaten up and had their properties damaged or destroyed, and in some extreme cases victims that cannot afford to repay their debts have committed suicide. We believe that to tackle this loan sharking issue in Malaysia, it is necessary to understand the cause motives that drive young people to join such treacherous and immoral industry. By investigating factors that contribute to choose loan sharking as occupation and or career, we could find effective ways to reduce young people interest or participation in such risky occupation. After reviewing Krumboltz’s, Holland’s and Super’s theory on career development; Super’s theory seemed the best as framework for understanding occupation/career choices among youth. Hence, this conference paper will focus on the description of Super’s career development theory as the framework to investigate the motives that drive young people in Malaysia to join such treacherous and immoral industry. The paper is a description of the research proposal for the study.